Palaeolithic Italy : Advanced studies on early human adaptations in the Apennine peninsula - Borgia, Valentina (SIdestone Press, 2018)
Intro -- Foreword -- Introduction -- Valentina Borgia & Emanuela Cristiani -- The Italian case in the context of the first European peopling -- Marta Arzarello -- Small Tools and the Palaeoloxodon- Homo interaction in the Lower Palaeolithic -- The contribution of use-wear analysis -- C. Lemorini -- Blade and bladelet reduction systems in the Italian Middle Paleolithic -- The case of Grotta del Cavallo, (Nardò - Lecce) -- Leonardo Carmignani, & Lucia Sarti -- The Lower Tyrrhenian Versant: was it a techno-cultural area during the Middle Palaeolithic? -- Evolution of the lithic industries of the Riparo del Molare sequence in the frame of Neanderthal peopling dynamics in Italy -- Daniele Aureli, & Annamaria Ronchitelli1 -- Neanderthal mobility pattern and technological organization in the Salento (Apulia, Italy) -- Enza Elena Spinapolice -- The socio-economic significance of Neanderthal shell technology -- A new perspective on Middle Palaeolithic adaptation to intertidal zones from disregarded tools -- Francesca Romagnoli -- The Middle-Upper Paleolithic transition interpreted through the Italian human remains -- Stefano Benazzi -- From Neanderthals to Anatomically Modern Humans in Liguria (Italy): the current state of knowledge -- Fabio Negrino & Julien Riel-Salvatore -- Human exploitation of avifauna during the Italian Middle and Upper Paleolithic -- Monica Gala, Ivana Fiore & Antonio Tagliacozzo -- Lithic raw material circulation and settlement dynamics in the Upper Palaeolithic of the Venetian Prealps (NE Italy) -- A key-role for palaeoclimatic and landscape changes across the LGM? -- Stefano Bertola, Federica Fontana1 & Davide Visentin1, -- Laminar tools with sinuous profile from Grotta Continenza (Trasacco - AQ, Italy) -- A specialized production from the Late Epigravettian levels -- Marco Serradimigni.